Best Answer

The 'answer' is the number that 'y' must be if the statement is true.

5 + 7y = 11 + 9y

Subtract 7y from each side of the equation:

5 = 11 + 2y

Subtract 11 from each side:

-6 = 2y

Divide each side by 2 :

-3 = y

Q: What is the answer to 5 plus 7y equals 11 plus 9y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

If: 5x-9y = 7 and 7y-3x = -5 Then: x = 1/2 or 0.5 and y = -1/2 or -0.5

Splitting the equation up into the two variables: x + 4x = 5x -7y + -2y = -9y Therefore, the simplified version is: 5x - 9y

9y-11=7 +11 +11 9y=18 y=2

(0,7)

9y = 12.6 y = 1.4

Related questions

10y = 9y + 4, so y = 4

If: 5x-9y = 7 and 7y-3x = -5 Then: x = 1/2 or 0.5 and y = -1/2 or -0.5

-9y + 8 = -91-9y = -91 -8-9y = -99y = -99-----9y = 11-99/-9 = 11 because -9X11 = -99

3x-2y+9+9y-x = 2x+7y+9

(3x - 7y)(2x + 9y)

9y subtract 11 equals 7

Splitting the equation up into the two variables: x + 4x = 5x -7y + -2y = -9y Therefore, the simplified version is: 5x - 9y

9y-11=7 +11 +11 9y=18 y=2

Y-8x plus 9y equals 10y-8x.

3x = 7y - 2 (subtract 3x and 7y to both sides of the first equation)9y = 4x + 1-7y = -3x - 2 (multiply by 4 each term of both sides of the first equation)9y = 4x + 1 (multiply by 3 each term of both sides of the second equation)-28y = -12x - 827y = 12x + 3 (add both equations)-y = -5 (multiply by -1 both sides)y = 53x = 7y - 2 (substitute 5 for y)3x = 7(5) - 23x = 33 (divide both sides by 3)x = 11Thus, the solution of the given system of the equations is x = 11 and y = 5.

7y + 2y = 9y 7y * 2y = 14y^2

4y - 6y + 9y = -2Combine like terms on the left side:7y = -2Divide each side by 7:y = -2/7The solution set is: { -2/7 }